Osteoporosis/Osteopenia in Post-Menopausal Breast Cancer Patients Receiving Hormonal Therapy - Khattak, Rahimullah; Ahmad, Riaz; Nadeem, Muhammad; Tufail, Umair; Khan, Amjad; Ahmad, Assam (Pakistan Armed Forces Medical Journal, 2022)
Objective: To analyze the presence of osteoporosis and osteopenia in post-menopausal breast cancer patients receiving hormonal therapy.Study Design: Comparative Cross-sectional Study.Place and Duration of Study: Oncology Department, Combined Military Hospital Rawalpindi Pakistan, from Dec 2020 to May 2021.Methodology: This study was conducted on 200 post-menopausal female breast cancer patients who had been taking Aromatase inhibitors for more than six months. All the study participants underwent a dual-energy X-ray absorptiometry (DEXA) scan to measure bone mineral density. As a result, they were classified as having osteoporosis or osteopenia based on bone mineral density. In addition, age, duration of therapy, tumour stage and molecular subtypes of breast cancer were correlated with the presence of osteopenia/osteoporosis in the study participants.Results: A total of 200 post-menopausal patients with breast cancer using hormonal therapy for more than six months were included in the final analysis. The mean age of the patients was 56.331 ± 6.744 years. In addition, 55 (22.5%) patients had normal bone mineral density, 92 (46%) had osteopenia, while 53 (26.5%) had osteoporosis on a dual-energy X-ray absorp- tiometry (DEXA) scan. Molecular subtypes of the tumour, the advancing age of patients and the long duration of hormonal therapy were statistically significantly associated with the presence of osteopenia/osteoporosis (p-value